Eling Lan Waspodo as A Local Perception for “Merapi” Volcanic Disaster Preparedness - Septian Aji Permana (Universitas Negeri Semarang, 2021)
Cangkringan community has a perception that the Merapi eruption is a gift not a threat or danger. This phenomenon can be understood as an attitude of wisdom of Merapi slopes to always be ready to live modestly with nature. This study aims to analyze the incidence of Merapi eruption in 2010 which has killed 347 peoples and found perceptions for readiness to face the threat of Merapi eruption in Cangkringan. This study used a qualitative approach for the perception of cangkringan peoples as preparedness to encounter the threat of Merapi eruption. Informant in this study were the Cangkringan peoples, caretaker of Mount Merapi, officials of Regional Disaster Management Agency (BPBD) in Sleman, Yogyakarta and data collected by observation and in-depth interviews. The collected data were then analyzed by using domain analysis, taxonomic, componential, and the theme of culture. The results showed that Perception built over the years was not to face the threat of Merapi eruption, but gratitude of Cangkringan community to the gift given by Merapi Volcano in the form of extraordinary natural wealth. Community’s perception of preparedness to face the threat of Merapi eruption in the form of advice or messages that contain high phylosophy value is eling lan waspodo. The presence of disasters are not preventable, but casualties can be minimized by preparedness action in facing the threat of Merapi eruption.